Cultural shifts in the symptoms of Anorexia Nervosa: The case of Orthorexia Nervosa. (1st March 2022) - Bhattacharya, Anushua; Cooper, Marita; McAdams, Carrie; Peebles, Rebecka; Timko, C. Alix
Abstract: Orthorexia Nervosa (ON) is a term describing a fixation on food purity, involving ritualized eating patterns and a rigid avoidance of "unhealthy foods." Those self-identified as having ON tend to focus on food composition and feel immense guilt after eating food deemed "unhealthy." Although not formally recognized as a psychiatric disorder by the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders ( DSM-5 ), ON has received increasing attention since its identification in 1997. There is ongoing work to establish diagnostic and empirical tools for measuring ON; embedded in this is the question as to whether or not ON is a new eating disorder. In this paper, we argue ON is not a new psychiatric disorder but rather a new cultural manifestation of anorexia nervosa (AN). We begin by providing an overview of historical representations and classification of eating disorders, with a specific focus on AN. This is followed by discussion of the rise in diet culture and healthism since the 19th century. We conclude by examining the diagnostic validity and utility of ON through a discussion of empirical evidence. Classifying ON under the diagnostic umbrella of AN may improve our understanding of factors underlying restrictive eating behaviors.